Reciprocal Relations Between Parenting and Adjustment in a Sample of Juvenile Offenders. - Williams, Lela Rankin; Steinberg, Laurence (Child Development)
A study examined the over-time reciprocal links between parenting and adolescent adjustment in a sample of 1,354 serious adolescent offenders followed for 3 years—16 years of age at baseline. Parallel processing growth curve models provided independent measurements of the effect of parenting on adolescent functioning as well as the effect of adolescent functioning on parenting. Positive adolescent development was aided by low parental hostility and high parental warmth. Parental monitoring predicted less problematic behavior, but also less positive functioning. Predictably, parents became amicable and warmer in response to positive adolescent development, and less warm in response to problematic adolescent functioning. Parental monitoring was reduced when adolescents showed either positive or problematic functioning.